The Endangered Species Act : history, implementation, successes, and controversies - Doub, J. Peyton (Open Access e-Books, 2013)
The complex regulations of the Endangered Species Act established by the U.S. Fish and Wildlife Service can be challenging for environmental professionals who must comply with them or assist clients in compliance. This is true especially for those without a background in biology or ecology. The Endangered Species Act: History, Implementation, Successes, and Controversies discusses the Act using clear scientific prose that all professionals whose activities fit into the ESA compliance process can readily comprehend, including those with limited education in science. The book begins by exploring.